Mendesain kelembagaan perantara nasional untuk memobilisasi pendanaan iklim di Indonesia: studi kasus BPDLH - Lubis, Ricky Karunia; Firmansyah, Amrie (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2025)
Climate finance plays a critical role in addressing climate change issues. Global donors have provided substantial funding to support developing countries cope with climate change. However, due to the limited technical capabilities and high political interference risks in developing countries, donors face difficulties in disbursing their funds. Therefore, the government should set up a national intermediary to bridge the needs and expectations of the donors and local-level project beneficiaries. This intermediary will help mobilize more finance toward local-level projects pertaining to the attainment of the climate agenda. This study employs a qualitative method with a scoping review approach to analyze the most fundamental challanges faced by global donors in deploying their climate funds to developing countries. In addition, this study proposes alternative solutions for government to accelerate the mobilization of such funds. The government of Indonesia (GoI) has established a national intermediary called the Indonesian Environmental Fund (IEF) which operates under the Ministry of Finance. However, the IEF still faces various obstacles in carrying out its role. Further improvement will help enhance IEF’s capacity in fundraising, promoting blended finance and stenghthening project implementation capabilities at the local level.